2017
DOI: 10.1186/s12883-017-0946-7
|View full text |Cite
|
Sign up to set email alerts
|

Evoked potentials after painful cutaneous electrical stimulation depict pain relief during a conditioned pain modulation

Abstract: BackgroundConditioned pain modulation (CPM) evaluates the pain modulating effect of a noxious conditioning stimulus (CS) on another noxious test stimulus (TS), mostly based solely on subjective pain ratings. We used painful cutaneous electrical stimulation (PCES) to induce TS in a novel CPM-model. Additionally, to evaluate a more objective parameter, we recorded the corresponding changes of cortical evoked potentials (PCES-EP).MethodsWe examined the CPM-effect in 17 healthy subjects in a randomized controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
50
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(71 citation statements)
references
References 52 publications
17
50
4
Order By: Relevance
“…With PCES as TS and cold water as CS we demonstrated a reduction of pain intensity during application of CS, which was accompanied by a signi cant decrease of PCES-EP amplitudes similar to our previous study 39 . The pain intensity of the cold water correlated with changes of PCESinduced pain; i. e. the more painful the conditioning stimulus was, the more pronounced it reduced the intensity of PCES-induced pain, though in contrast to the ndings of our pilot study 39 the results were not signi cant after correction for multiple comparisons. Also, the signi cant correlation between pain intensity of the cold water and ratios of PCES-EP amplitudes 39 was not found in the present study.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…With PCES as TS and cold water as CS we demonstrated a reduction of pain intensity during application of CS, which was accompanied by a signi cant decrease of PCES-EP amplitudes similar to our previous study 39 . The pain intensity of the cold water correlated with changes of PCESinduced pain; i. e. the more painful the conditioning stimulus was, the more pronounced it reduced the intensity of PCES-induced pain, though in contrast to the ndings of our pilot study 39 the results were not signi cant after correction for multiple comparisons. Also, the signi cant correlation between pain intensity of the cold water and ratios of PCES-EP amplitudes 39 was not found in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…In summary, using the recently introduced novel CPM-paradigm we demonstrated that both PCES-induced pain and PCES-EP amplitudes can be reduced not only by CPM 20,39 but also during distraction by a cognitive task. While the amount of pain relief induced by CPM and distraction by a cognitive task did not differ signi cantly during both interventions, the decrease of PCES-EP amplitudes after distraction by a cognitive task was slightly more pronounce than during CPM.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Using “pain inhibits pain” models, CPM is tested using a noxious conditioning stimulus (CS) to influence another painful test stimulus (TS), upon which the analgesic effect is tested (Nir & Yarnitsky, 2015; Yarnitsky, 2010). The TS is typically of short duration, milliseconds to seconds, during which the pain response is typically recorded by means of subjective pain ratings or nociceptive withdrawal reflexes (RIII reflex) elicited by painful stimuli to the sural nerve (Jurth, Rehberg, & von Dincklage, 2014) and more recently by changes of cortical evoked brain potentials (Höffken, Özgül, Enax-Krumova, Tegenthoff, & Maier, 2017). The CPM effect correspond to the CS-induced changes in these pain responses.…”
Section: Assessment Of Endogenous Cpmmentioning
confidence: 99%